Recurrent Pregnancy Wastage: Histology of Products of Conception - Ramraje, Sushma; Vadnere, Mrunal (Annals of Pathology and Laboratory Medicine, 2018)
Background: Histopathologic examination of products of spontaneous abortion is done to identify pregnancy- molar or ectopic. Also, in the perspective of recurrent abortion, additional diagnostic information can be obtained. We studied products of conception with the aim to find if it is of any value in recurrent pregnancy wastage. Methods: Data was obtained from patients with the diagnosis of recurrent spontaneous abortion. The samples were examined macroscopically and microscopically by a competent histopathologist. Results: Age of the patients ranged from 23-36 years. Majority of the recurrent abortions occurred during 10-15 weeks of gestation accounting for 41 (65.07%) cases. Recurrences ranged from third to fifth time loss contributing to 44 (69.84%), 14 (22.22%) and 5 (7.93%) cases respectively. Villous oedema of chorionic villi were seen in 30 (47.61%) cases. Abnormal vascularity in the form of complete avascularity of villi was observed in 8 (12.69%) cases. 50 (79.36%) cases showed fibrinoid degeneration. Amongst the 50 cases, 30 (60%) cases showed both perivillous and intravillous fibrin while 20 (40%) cases showed only perivillous fibrin deposition. 30 cases (47.61%) showed evidence of chronic villitis. The 30 cases were subdivided into “infectious villitis“ and “villitis of unknown etiology“ (VUE). Infectious villitis was seen in only 1 case (3.3%) which showed presence of toxoplasmal cysts and plasma cell infiltration. Deciduitis was observed in 31 (49.20%) cases. Decidual necrosis was seen in 23 (36.50%) cases. 3 (4.76%) cases of partial mole were diagnosed. 4 (6.34%) cases each of syncitial knots and villous infarction were seen. We did not encounter any cases of chronic intervillositis and chronic endometritis. Conclusion: It is rational to perform histopathological examination routinely for all recurrent miscarriages.